Spain and the Palestinian Sephardim in the 19th century - Sbaihat, Ahlam (Anaquel de Estudios Árabes, 2018)
In 1793, Spain resumed diplomacy with the Ottoman Empire and established consulates in its principal cities, among them Jerusalem and Haifa. There is a lack of studies regarding the Palestinian Sephardim through the 19th century and their relationship with these consulates, so this study aims to carry out a historical analysis of contemporary sources and existing references to assess the nature of this relationship. The results indicate that, due to the political and economic situation in Spain, only the pilgrims, missionaries, traders and non-Palestinian Sephardim with Spanish citizenship or protected by Spain received diplomatic protection and interest by the consulates.
Keywords: Jerusalem; Judaism; Holy Lands; Ottoman Empire; Consulate of Spain